Preparation method and application of lithium iron phosphate nanofiber

By using lithium iron phosphate carbon nanofibers as electrode materials, the problems of low electrode selectivity and poor circulation performance in the prior art are solved, and efficient lithium extraction and good circulation performance are achieved.

CN119900108APending Publication Date: 2025-04-29湖南工商大学
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510194248.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

In the prior art, the electrode selectivity is low and the circulation performance is poor, making it difficult to efficiently extract lithium ions in salt lake brine.

Method used

Lithium iron phosphate carbon nanofibers are used as electrode material to prepare nanofiber precursor materials by electrospinning, and pre-oxidation and calcination are performed to obtain lithium iron phosphate carbon nanofibers. This material is used as a cathode material and activated carbon as an anode material, and is used in the electrochemical lithium extraction process.

Benefits of technology

It has achieved efficient lithium extraction, excellent lithium ion selectivity and circulation performance, and its adsorption capacity reaches 15.27 mg/g, and its capacity retention rate is 95% after 10 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900108A_ABST
    Figure CN119900108A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium extraction, in particular to a preparation method and application of lithium iron phosphate nanofibers. According to the specific technical scheme, the method comprises the following steps: (1) dissolving a phosphorus source, an iron source and a lithium source in DMF (Dimethyl Formamide) to obtain a solution A; dissolving the fiber material in DMF to obtain a solution B, uniformly mixing the solution A and the solution B to obtain a spinning solution, and performing electrostatic spinning to obtain a nanofiber precursor material; and (2) pre-oxidizing the nanofiber precursor material for 2-4 hours at the temperature of 250-280 DEG C, heating to 800 DEG C in an inert atmosphere, calcining for 10 hours, and cooling to room temperature to obtain the lithium iron phosphate carbon nanofiber. The invention solves the problems of complex process, low lithium extraction selectivity and poor circularity in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium extraction, and in particular to a preparation method and application of lithium iron phosphate nanofibers. Background Art

[0002] With the continuous development of new energy power batteries and energy storage equipment, the demand for lithium ions continues to grow, and will continue to maintain a growth trend for a long time. Compared with lithium extraction from ore, the resources, cost advantages and smaller environmental impact of salt lake brine will be the main development focus in the future. Salt lake brine contains rich resources such as lithium, boron, rubidium, cesium, and bromine, but the lithium content of salt lake brine is generally low, such as high content of impurities such as K, Na, Ca, and Mg, which makes extraction difficult. Therefore, it is of great significance to develop more efficient lithium extraction technology.

[0003] Traditional methods such as precipitation, extraction, and adsorption are the most widely used production technologies in industry, but the process is long and inefficient. Environmental impact assessment and treatment in the entire process, such as the impact of huge freshwater consumption in the desorption process on the regional water environment, the ecological sustainable development of evaporation and concentration of brine, and organic or heavy metal pollution left by the extraction / desorption cycle, have seriously hindered its application in lithium extraction from brine. Membrane separation technologies such as nanofiltration and electrodialysis have achieved good results in lithium extraction from brine, but cost and membrane pollution have always been the main problems that plague the industrial process.

[0004] The electrochemical method of extracting lithium from brine or seawater has the characteristics of high efficiency and low energy consumption, and has attracted much research attention in recent years. In the separation stage, the lithium in the brine is adsorbed and embedded in the working electrode, and then released into the enriched solution by exchanging electrodes or current, such as electrodialysis and "rocking chair battery" technologies, which are essentially lithium ion deintercalation and electron transfer. Although the one-step lithium extraction process can be achieved, it cannot achieve the separation of ions of the same valence, so the right working electrode material is the key.

[0005] In view of this, it is necessary to provide a preparation method and application of lithium iron phosphate carbon nanofibers to solve or at least alleviate the technical defects of low electrode selectivity and poor cycle performance in the above-mentioned prior art. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing lithium iron phosphate nanofibers and applications thereof, which solves the problems of complex procedures, low lithium extraction selectivity and poor cyclability in the prior art.

[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0008] The present invention discloses a method for preparing lithium iron phosphate nanofibers, the steps of which are as follows:

[0009] (1) dissolving a phosphorus source, an iron source, and a lithium source in DMF to obtain a solution A; dissolving a fiber material in DMF to obtain a solution B, mixing the solution A and the solution B evenly to obtain a spinning solution, and performing electrostatic spinning to obtain a nanofiber precursor material;

[0010] (2) The nanofiber precursor material is pre-oxidized for 2 to 4 hours at a temperature of 250 to 280° C., then heated to 800° C. in an inert atmosphere and calcined for 10 hours, and then cooled to room temperature to obtain lithium iron phosphate carbon nanofibers.

[0011] Preferably, the molar ratio of the phosphorus source, the iron source and the lithium source is 1:1:1, and the mass concentration of the fiber material is 10-14%.

[0012] Preferably, the phosphorus source may be any one of phosphoric acid and ammonium hydrogen phosphate, the iron source may be any one of ferric nitrate, ferrous acetate and ferrous sulfate, and the lithium source may be any one of lithium hydroxide, lithium acetate, lithium nitrate and lithium carbonate.

[0013] Preferably, the fiber material is one or more of polyacrylonitrile fiber, polyvinyl chloride fiber, and polyvinylidene fluoride fiber.

[0014] Correspondingly, the lithium iron phosphate nanofibers prepared by the above preparation method are used in extracting lithium.

[0015] Preferably, lithium iron phosphate carbon nanofibers are used as cathode material and activated carbon is used as anode material to extract lithium from lithium-containing brine.

[0016] Preferably, the lithium-containing brine Li + The concentration is 0.1~1g / L and the pH value is 5.5~8.

[0017] Preferably, the lithium-containing brine also contains Mg 2+ .

[0018] Preferably, after the lithium iron phosphate carbon nanofibers extract lithium ions from the lithium-containing brine, the lithium iron phosphate carbon nanofibers are subjected to a lithium removal treatment.

[0019] Preferably, the delithiation process is as follows: using lithium iron phosphate carbon nanofibers as the positive electrode, activated carbon as the negative electrode, and using a neutral solution as a desorption solution to desorb the adsorbed lithium ions.

[0020] Preferably, the neutral solution includes water or lithium chloride solution; when it is a lithium chloride solution, the concentration of lithium ions in the lithium chloride solution is not higher than 0.5 mmol / L.

[0021] The present invention has the following beneficial effects:

[0022] 1. The present invention prepares a specific lithium selective electrode (lithium iron phosphate carbon nanofiber) as the negative electrode of capacitive deionization and performs an electrochemical treatment process to achieve the separation and extraction of lithium from lithium-containing brine; then, by simply reversing the electrode, lithium removal can be performed in a neutral solution (such as a deionized water solution) to obtain a lithium-rich solution.

[0023] 2. The present invention has excellent lithium extraction efficiency and lithium ion selectivity; and the present invention can also perform cyclic lithium extraction based on lithium iron phosphate carbon nanofibers; the adsorption capacity of the lithium iron phosphate carbon nanofibers in the present invention can reach 15.27 mg / g, and after 10 cycles, the capacity retention rate is 95%. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a scanning electron microscope (SEM) image of the product prepared in Example 1 magnified 30,000 times;

[0025] Figure 2 is the XRD pattern of the product prepared in Example 1;

[0026] Figure 3 The electrosorption cycle performance of the product prepared in Example 1;

[0027] Figure 4 is the selective adsorption performance of the product prepared in Example 1;

[0028] Figure 5 This is a scanning electron microscope (SEM) image of the product prepared in Comparative Example 1 magnified 30,000 times. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0031] The present invention discloses a method for preparing lithium iron phosphate nanofibers, the steps of which are as follows:

[0032] (1) A phosphorus source, an iron source, and a lithium source are dissolved in dimethylformamide (DMF) to obtain a solution A; a fiber material is dissolved in DMF to obtain a solution B, and the solution A and the solution B are mixed evenly to obtain a spinning solution, and a nanofiber precursor material is obtained by electrostatic spinning; wherein the molar ratio of the phosphorus source, the iron source, and the lithium source is 1:1:1, and as an embodiment, the amount of the phosphorus source, the iron source, and the lithium source added is 0.006 to 0.008 mol, respectively, and the mass concentration of the fiber material is 10 to 14%. The phosphorus source can be any one of phosphoric acid and ammonium hydrogen phosphate, the iron source can be any one of ferrous nitrate, ferrous acetate, and ferrous sulfate, and the lithium source can be any one of lithium hydroxide, lithium acetate, lithium nitrate, and lithium carbonate. The fiber material is one or more of polyacrylonitrile fiber (PAN), polyvinyl chloride fiber (PVC), and polyvinylidene fluoride fiber (PVDF).

[0033] (2) The nanofiber precursor material is pre-oxidized in a tube furnace for 2 to 4 hours at a temperature of 250 to 280° C. and a heating rate of 2° C. / min, and then heated to 800° C. at a heating rate of 2° C. / min in an inert atmosphere and calcined for 10 hours, and cooled to room temperature to obtain lithium iron phosphate carbon nanofibers. The inert atmosphere is a nitrogen or argon atmosphere.

[0034] The invention discloses the application of the prepared lithium iron phosphate nanofibers in extracting lithium, specifically adopting a capacitive deionization method to selectively extract lithium.

[0035] The selective lithium extraction process is as follows: lithium iron phosphate carbon nanofibers are used as cathode materials, activated carbon is used as anode materials, a DC power supply is applied with a voltage of 1.2V, and the effective area of ​​the positive and negative electrodes is 2×2cm, and lithium is extracted from lithium-containing brine. + The concentration of Mg is 0.1-1 g / L, and the pH value is 5.5-8, preferably 6-8. The lithium-containing brine also contains Mg 2+ , where Mg 2+ The concentration can reach 1-20 g / L. The flow rate of the lithium-containing brine is 1-10 mL / min, and the lithium-containing brine is circulated until the lithium concentration does not change much, thus completing the lithium extraction process.

[0036] Delithiation: After the lithium iron phosphate carbon nanofiber extracts the lithium ions from the lithium-containing brine, the lithium iron phosphate carbon nanofiber is subjected to a delithiation treatment. The delithiation treatment process is as follows: the electrodes after the lithium extraction treatment are reversed, the lithium iron phosphate carbon nanofiber is used as the positive electrode (or anode), the activated carbon is used as the negative electrode (or cathode), a DC power supply is used to apply a voltage of 1.2V, a neutral solution is used as the desorption solution, and the flow rate of the neutral solution is 1 to 10mL / min, and the treatment is circulated until the lithium concentration in the solution does not change much, thereby completing the desorption of the lithium ions adsorbed in the lithium iron phosphate carbon nanofiber, thereby completing the extraction of lithium ions from the lithium-containing brine, and allowing the lithium iron phosphate carbon nanofiber to be reused after the delithiation treatment.

[0037] Furthermore, the neutral solution includes water or lithium chloride solution; when it is a lithium chloride solution, the concentration of lithium ions in the lithium chloride solution is not higher than 0.5 mmol / L.

[0038] Furthermore, the present invention uses lithium iron phosphate carbon nanofiber as the membrane electrode material of CDI to assemble a lithium extraction device, which is a capacitive deionization (CDI) device, which includes an organic glass plate, a silicone gasket, a current collector, lithium iron phosphate carbon nanofiber as a negative electrode material, activated carbon as a positive electrode material, a DC power supply, and an ion exchange membrane. + The concentration is 0.1~1g / L.

[0039] The specific process of lithium extraction is: the lithium-containing brine flows through the capacitor deionization device at a flow rate of 1 to 10 mL / min. During this process, the charging voltage of the DC power supply is 1.2V, and the effective area of ​​the electrode is 2 cm×2 cm. The lithium-containing brine circulates in the device until the lithium ion concentration does not change much. The lithium iron phosphate carbon nanofibers and activated carbon electrodes after lithium extraction are reversed and de-lithium is removed in deionized water or lithium chloride solution. The flow rate of deionized water or lithium chloride solution is 1 to 10 mL / min, and the circulation process is carried out until the lithium concentration in the solution does not change much.

[0040] The present invention will be further described below in conjunction with specific embodiments.

[0041] Example 1

[0042] 1. Preparation of selective electrode materials:

[0043] (1) Obtaining nanofiber substrate material: 0.007 mol iron nitrate Fe(NO3)3·9H2O, 0.007 mol lithium acetate C2H3O2Li·2H2O, and 0.007 mol phosphoric acid H3PO4 were dissolved in 29 g DMF and stirred for 4 h until a homogeneous solution was formed to obtain solution A; 6 g PAN was dissolved in 29 g DMF solution and stirred for 4 h until a homogeneous solution was formed to obtain solution B; solution A and solution B were mixed and stirred for 4 h to obtain a precursor spinning solution; lithium iron phosphate nanofiber precursor material was obtained by electrospinning for 10 h. The electrospinning conditions were: spinning voltage 18 KV, flow rate 1 mL / min, distance between needle tip and roller 15 cm, humidity 46%, and temperature 25 °C.

[0044] (2) Preparation of lithium iron phosphate carbon nanofiber material: The obtained lithium iron phosphate nanofiber precursor material was hot pressed at a temperature of 180°C, a pressure of 1.5 MPa, and a time of 40 min; then it was taken out and naturally cooled, and then transferred to a tubular furnace, pre-oxidized at 260°C in air for 2 h, with a heating rate of 2°C / min, and then calcined at 800°C in nitrogen / argon for 10 h. After naturally cooling to room temperature, the lithium iron phosphate carbon nanofiber material was obtained, and its specific surface area was 257.4 m 2 / g, its SEM picture is as follows Figure 1 As shown in Figure 2, lithium phosphate dendrite particles were uniformly synthesized on the surface of nanofibers. Figure 2 The XRD results show that the attachment on the fiber surface is lithium iron phosphate after comparison with the standard PDF card. 2. The electrochemical extraction process of lithium ions of the prepared product:

[0045] The CDI system consists of a plexiglass base plate, a silicone gasket, a current collector, an electrode, and an ion exchange membrane, with an effective area of ​​2×2 cm. The lithium iron phosphate carbon nanofiber membrane is cut into a square size of 3×3 cm and used as the negative electrode material. The porous carbon electrode is used as the positive electrode material, and the voltage is 1.2V.

[0046] The lithium extraction solution is a laboratory simulated lithium chloride solution, Li + The initial concentration of lithium iron phosphate carbon nanofibers was 100 mg / L, and the pH of the simulated solution was 6.5. The simulated solution was injected into the CDI system at 10 mL / min through a peristaltic pump and processed by circulating filtration until the lithium ion concentration in the solution no longer changed significantly. The results showed that the adsorption performance of lithium iron phosphate carbon nanofibers for lithium was 15.27 mg / g.

[0047] 3. Lithium iron phosphate carbon nanofiber recycling:

[0048] After the lithium extraction process is completed, the positive and negative electrodes of the CDI are reversed, the voltage is 1.2V, deionized water is used as the desorption solution, and a peristaltic pump is used to circulate and inject it into the CDI system at a flow rate of 10mL / min until the lithium concentration changes little, and a concentrated lithium-rich solution is obtained; after the desorption is completed, the electrodes are reversed, and lithium iron phosphate carbon nanofibers are used as the negative electrode material to enter the next cycle.

[0049] The results are as follows Figure 3 As shown, the results show that after 10 cycles, the adsorption capacity of lithium iron phosphate carbon nanofibers is 14.5 mg / g, and 95% of the adsorption capacity is still maintained.

[0050] Example 2

[0051] The difference between this embodiment and embodiment 1 is that the polyacrylonitrile fiber is changed to polyvinylidene fluoride fiber, and the other conditions are the same as those in embodiment 1.

[0052] Finally, the specific surface area of ​​the prepared lithium iron phosphate carbon nanofiber material is 232.9 m 2 / g,

[0053] The lithium iron phosphate carbon nanofiber material prepared in this example is used as the negative electrode material, and the other conditions are the same as those in Example 1. The results show that the adsorption performance of lithium iron phosphate carbon nanofiber to lithium is 14.77 mg / g. After 10 cycles, the adsorption capacity of lithium iron phosphate carbon nanofiber is 12.9 mg / g, and the adsorption capacity is still maintained at 87%.

[0054] Example 3

[0055] The difference between this embodiment and embodiment 1 is that the concentrations of the lithium source, phosphorus source and iron source are adjusted to 0.006 mol, and the other conditions are the same as those in embodiment 1.

[0056] Finally, the specific surface area of ​​the prepared lithium iron phosphate carbon nanofiber material is 199.4 m 2 / g,

[0057] The lithium iron phosphate carbon nanofiber material prepared in this example is used as the negative electrode material, and the other conditions are the same as those in Example 1. The results show that the adsorption performance of lithium iron phosphate carbon nanofiber to lithium is 12.16 mg / g. After 10 cycles, the adsorption capacity of lithium iron phosphate carbon nanofiber is 11.4 mg / g, and 93% of the adsorption capacity is still maintained.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 1 is that the concentration of polyacrylonitrile is adjusted, the amount of polyacrylonitrile used is 8 g, and the other conditions are the same as those in embodiment 1.

[0060] Finally, the specific surface area of ​​the prepared lithium iron phosphate carbon nanofiber material is 223.9 m 2 / g,

[0061] The lithium iron phosphate carbon nanofiber material prepared in this example is used as the negative electrode material, and the other conditions are the same as those in Example 1. The results show that the adsorption performance of lithium iron phosphate carbon nanofiber to lithium is 13.7 mg / g. After 10 cycles, the adsorption capacity of lithium iron phosphate carbon nanofiber is 12.4 mg / g, and 90% of the adsorption capacity is still maintained.

[0062] Example 5

[0063] 1. The preparation of the selective electrode material is the same as in Example 1.

[0064] 2. Electrochemical extraction of lithium ions: Compared with Example 1, the only difference is that the simulated solution is adjusted to a mixed solution of Li and Mg, and the other conditions are the same as Example 1. + The initial concentration of Mg was 100 mg / L, 2+ The initial concentration was 1000 mg / L and the pH of the simulated solution was 6.5. The results showed that the adsorption performance of lithium iron phosphate carbon nanofibers for lithium and magnesium were 14.7 mg / g and 1.88 mg / g respectively.

[0065] 3. Lithium iron phosphate carbon nanofiber recycling: Same as Example 1. The results are as follows Figure 4 As shown, the results show that after 10 cycles, the adsorption capacity of lithium iron phosphate carbon nanofibers is 13.5 mg / g, and 91.8% of the adsorption capacity is still maintained.

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 1 is that no lithium iron phosphate nano-dendrites are formed on the surface of the polyacrylonitrile fiber. The specific preparation is as follows:

[0068] 1. Preparation of comparative fiber materials:

[0069] 6 g of PAN was dissolved in 29 g of DMF solution and mixed evenly with 29 g of DMF solution to obtain a spinning solution; PAN nanofibers were prepared by electrospinning, and after hot pressing (same as in Example 1), they were transferred to a tubular furnace and pre-oxidized at 260°C in air for 2 h with a heating rate of 2°C / min, and then calcined at 800°C in nitrogen / argon for 10 h with a heating rate of 2°C / min, and naturally cooled to room temperature (same as in Example 1).

[0070] The SEM image of the material prepared in this comparative example is as follows: Figure 5 As shown in Figure 2, the prepared fiber surface remains smooth, no lithium iron phosphate nanoparticles are generated, and the specific surface area is 92.4 m 2 / g.

[0071] 2. Electrochemical extraction process of lithium ions:

[0072] Compared with Example 1, the only difference is that the comparative material is used as the negative electrode material, and the other conditions are the same as Example 1.

[0073] In this comparative example, the adsorption performance of the comparative fiber material for lithium is 1.27 mg / g.

[0074] Comparative Example 2

[0075] The only difference between this comparative example and Example 1 is that different concentrations of lithium source, phosphorus source and iron source are used to prepare the selective electrode material.

[0076] 1. Preparation of selective electrode materials:

[0077] Obtain nanofiber substrate material: 0.004 mol iron nitrate Fe(NO3)3·9H2O, 0.004 mol lithium acetate C2H3O2Li·2H2O, and 0.004 mol phosphoric acid H3PO4 are dissolved in 29 g DMF and stirred for 4 h until a homogeneous solution is formed to obtain solution A; 6 g PAN is dissolved in 29 g DMF solution and stirred for 4 h until a homogeneous solution is formed to obtain solution B; solution A and solution B are mixed and stirred for 4 h to obtain a precursor spinning solution (same as Example 1).

[0078] In this comparative example, no lithium iron phosphate nanoparticles were generated on the fiber surface, and the specific surface area was 98.6 m 2 / g.

[0079] 2. Electrochemical extraction process of lithium ions:

[0080] Compared with Example 1, the only difference is that the comparative material is used as the negative electrode material, and the other conditions are the same as Example 1.

[0081] In this comparative example, the adsorption performance of the comparative fiber material for lithium is 1.03 mg / g.

[0082] Comparative Example 3

[0083] The only difference between this comparative example and Example 1 is that PAN solutions of different concentrations are used to prepare the selective electrode materials.

[0084] 1. Preparation of selective electrode materials:

[0085] Obtain nanofiber substrate material: 0.007 mol iron nitrate Fe(NO3)3·9H2O, 0.007 mol lithium acetate C2H3O2Li·2H2O, and 0.007 mol phosphoric acid H3PO4 are dissolved in 29 g DMF and stirred for 4 h until a homogeneous solution is formed to obtain solution A; 10 g PAN is dissolved in 29 g DMF solution and stirred for 4 h until a homogeneous solution is formed to obtain solution B; solution A and solution B are mixed and stirred for 4 h to obtain a precursor spinning solution (same as Example 1).

[0086] In this comparative example, no lithium iron phosphate nanoparticles were generated on the fiber surface, and the specific surface area was 96.1 m 2 / g.

[0087] 2. Electrochemical extraction process of lithium ions:

[0088] Compared with Example 1, the only difference is that the comparative material is used as the negative electrode material, and the other conditions are the same as Example 1.

[0089] In this comparative example, the adsorption performance of the comparative fiber material for lithium is 1.25 mg / g.

[0090] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing lithium iron phosphate nanofibers, characterized in that: Here are the steps: (1) dissolving a phosphorus source, an iron source, and a lithium source in DMF to obtain a solution A; dissolving a fiber material in DMF to obtain a solution B, mixing the solution A and the solution B evenly to obtain a spinning solution, and performing electrostatic spinning to obtain a nanofiber precursor material; (2) The nanofiber precursor material is pre-oxidized for 2 to 4 hours at a temperature of 250 to 280° C., then heated to 800° C. in an inert atmosphere and calcined for 10 hours, and then cooled to room temperature to obtain lithium iron phosphate carbon nanofibers.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the phosphorus source, the iron source and the lithium source is 1:1:1, and the mass concentration of the fiber material is 10-14%.

3. The preparation method according to claim 1 or 2, characterized in that: The fiber material is one or more of polyacrylonitrile fiber, polyvinyl chloride fiber, and polyvinylidene fluoride fiber.

4. Use of lithium iron phosphate nanofibers prepared by the preparation method according to any one of claims 1 to 3 in extracting lithium.

5. The use according to claim 4, characterized in that: Lithium iron phosphate carbon nanofibers are used as cathode materials and activated carbon as anode materials to extract lithium from lithium-containing brine.

6. The preparation method according to claim 4, characterized in that: The lithium-containing brine Li + The concentration is 0.1~1g / L and the pH value is 5.5~8.

7. The use according to claim 5, characterized in that: The lithium-containing brine also contains Mg 2+ .

8. The use according to claim 5, characterized in that: After the lithium iron phosphate carbon nanofibers extract lithium ions from the lithium-containing brine, the lithium iron phosphate carbon nanofibers are subjected to a lithium removal treatment.

9. The use according to claim 8, characterized in that: The delithiation process is as follows: using lithium iron phosphate carbon nanofiber as the positive electrode, activated carbon as the negative electrode, and a neutral solution as the desorption solution to desorb the adsorbed lithium ions.

10. The use according to claim 9, characterized in that: The neutral solution includes water or lithium chloride solution; when it is lithium chloride solution, the concentration of lithium ions in the lithium chloride solution is not higher than 0.5 mmol / L.